Assessing Management Practices Influencing Performance of Civil Servants at Gamogo Sub County Kapchorwa District - Stella Joan Chebet (Uganda Christian University, 2025)
This research report was undertaken to assess management practices influencing performance of civil servants at Gamogo sub county, Kapchorwa district and it was carried out with the help of three specific objectives, that is; to investigate the influence of clear communication channels on performance of civil servants at Gamogo sub county, Kapchorwa district, to assess the influence of supervision on performance of civil servants at Gamogo sub county, Kapchorwa district, to examine the influence of merit-based promotion on performance of civil servants at Gamogo sub county, Kapchorwa district. The researcher used a sample size of 63 respondents and used questionnaires to collect data and later the data was analyzed using the statistical package for social sciences (SPSS). Results of the first objective showed that clear communication channels has a significant effect on performance of civil servants at Gamogo sub county, kapchorwa district; 54% of the respondents were positive to the statement that effective communication skills enable civil servants to convey information clearly and professionally; 62% were positive to the statement that a feedback mechanism encourages two-way communication for continuous improvement; 61% of the respondents were positive to the statement that adaptability allows civil servants to adjust communication styles for different audiences. Results of the second objective revealed that supervision has a significant effect on performance of civil servants at Gamogo sub county, kapchorwa district. Supported by the following responses; 80% of the respondents were positive to the statement that regular feedback helps civil servants improve their performance and efficiency, it can be observed that 57% were positive to the statement that performance evaluation identifies strengths, weaknesses, and areas for improvement, 51% were positive to the statement that conflict resolution by supervisors promotes teamwork and a positive work environment. Results of the third objective showed that merit-based promotion has a significant effect on performance of civil servants at Gamogo sub-county, Kapchorwa district. 62% forming the majority of respondents were positive to the statement that fair promotion processes enhance job satisfaction and reduce workplace conflicts. There is need for the government to strengthen supervision structures by establishing clear guidelines, roles, and responsibilities for supervisors at all levels. This can be achieved by developing a comprehensive supervision framework that is well-resourced and supported by relevant legal and policy instruments.